Preferential targeting of i-motifs and G-quadruplexes by small molecules. Issue 11 (19th September 2017) - Debnath, Manish; Ghosh, Shirsendu; Chauhan, Ajay; Paul, Rakesh; Bhattacharyya, Kankan; Dash, Jyotirmayee
Abstract : Ligand-dependent regulation of gene expression has been delineated by targeting i-motifs and G-quadruplexes. Abstract : i-Motifs and G-quadruplexes are dynamic nucleic acid secondary structures, which are believed to play key roles in gene expression. We herein report two peptidomimetic ligands (PBP1 andPBP2 ) that selectively target i-motifs and G-quadruplexes over double-stranded DNA. These peptidomimetics, regioisomeric with respect to the position of triazole/prolinamide motifs, have been synthesized using a modular method involving Cu(i )-catalyzed azide and alkyne cycloaddition. The para -isomer, PBP1 exhibits high selectivity for i-motifs while the meta -isomerPBP2 binds selectively to G-quadruplex structures. Interestingly, these ligands have the ability to induce G-quadruplex or i-motif structures from the unstructured single-stranded DNA conformations, as observed using single molecule Förster resonance energy transfer (smFRET) studies. The quantitative real-time polymerase chain reaction (qRT-PCR), western blot, and dual-luciferase assays indicate thatPBP1 upregulates andPBP2 downregulates BCL-2 gene expression in cancer cells.